Discourse on Religious Moderation in the View of Surakarta Students According to Indonesian Law - Mahfiana, Layyin; Ariyani, Evi; Lisma, Lisma (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2024)
Religious moderation is very important because the tendency of excessive or excessive religious experiences often leaves one-sided claims of truth and considers themselves the most right while others are wrong. Based on the above background, the researcher is interested in studying the extent of understanding of religious moderation among Surakarta students and how efforts are made to increase awareness of religious moderation among students. This type of research is field research with a qualitative approach that aims to describe the data obtained in the field regarding students' understanding related to religious moderation. The data sources used in this study are primary and secondary. The data collection techniques used were interviews and documentation. Students' understanding of religious moderation varied greatly from the results of several interviews conducted with 30 students in the Islamic Criminal Law Study Program, 20 students explained that moderation is tolerance and mutual respect between religious people.Â This is not wrong, because one of the indicators of religion is tolerance. Meanwhile, the other 10 students have understood that moderation is our perspective or attitude in religion in moderation, understanding and practicing religious teachings that are not extreme. Meanwhile, 30 students of the Law Study Program at the Batik University of Surakarta most of them do not understand what religious moderation is in terms of terminology, but once they are given an understanding and indicators related to religious moderation, they understand. Most of them have been taught in Pancasila and Civic Education courses. Religious moderation can be used as a learning approach so that students can think critically and analyze the courses they are taught, which of course remains based on the principles of religious moderation.